The genus Inula and their metabolites : From ethnopharmacological to medicinal uses - Seca, Ana M. L. (2014)
ETHNOPHARMACOLOGICAL RELEVANCE: The genus Inula comprises more than one hundred species widespread in temperate regions of Europe and Asia. Uses of this genus as herbal medicines have been first recorded by the Greek and Roman ancient physicians. In the Chinese Pharmacopoeia, from the 20 Inula spp. distributed in China, three are used as Traditional Chinese medicines, named Tumuxiang, Xuanfuhua and Jinfeicao. These medicines are used as expectorants, antitussives, diaphoretics, antiemetics, and bactericides. Moreover, Inula helenium L. which is mentioned in Minoan, Mycenaean, Egyptian/Assyrian pharmacotherapy and Chilandar Medical Codex, is good to treat neoplasm, wound, freckles and dandruff. Many other Inula spp. are used in Ayurvedic and Tibetan traditional medicinal systems for the treatment of diseases such as bronchitis, diabetes, fever, hypertension and several types of inflammation. This review is a critical evaluation of the published data on the more relevant ethnopharmacological and medicinal uses of Inula spp. and on their metabolites biological activities. This study allows the identification of the ethnopharmacological knowledge of this genus and will provide insight into the emerging pharmacological applications of Inula spp. facilitating the prioritirization of future investigations. The corroboration of the ethnopharmacological applications described in the literature with proved biological activities of Inula spp. secondary metabolites will also be explored.